Flexible working arrangements on employee performance in Public Universities in Mount Kenya region - Mwiti, Mercy Kanyua (Meru; Meru University of Science and Technology, 2023)
The study sought to identify the effect of flexible working arrangements on employee performance in public universities in the Mount Kenya region. The Objectives of the study were: to determine the extent to which job sharing affects the performance of employees in public universities in Mount Kenya region; to determine how remote/teleworking affects employee performance of Public Universities in Mount Kenya region; to determine the extent to which compressed work schedules affects employee performance of public Universities in Mount Kenya region. The study was guided by the hypothesis: There is no statistically significant relationship between job sharing and employee performance of public universities in the Mount Kenya region; There is no statistically significant relationship between remote/teleworking and employee performance of public Universities in Mount Kenya region; There is no statistically significant relationship between compressed work schedules and employee performance in public Universities in Mount Kenya region. The target populations of the study were 3,012 employees of public Universities in the Mount Kenya region consisting of teaching and non-teaching staff. The sample size was 353 respondents determined by the use of Yumane formulae. The study employed a descriptive research design. The open-ended questionnaire was used as the main data collection instrument. Data analysis and interpretation was based on descriptive statistics and inferential statistics. In addition, a multiple regression model was used to explore the relationship between the variables under study. A pilot test will be carried out in a public University outside Mount Kenya region to ensure validity and reliability of the data collection instruments prior to the actual collection of data. The data were analyzed using SPSS software version 28. Descriptive statistics were presented in frequency tables, percentages, mean, standard deviations, and graphs. Inferential statistics were used in testing null hypotheses. Results showed that job sharing and employee performance in public universities were positively and significantly related (gb(B=0.247, p=0.000). In addition, teleworking and employee performance of public universities were positively and significantly related (gb(B=0.380, p=0.000). Further results revealed that compressed work schedules and employee performance of public universities were positively and significantly related (gb(B=0.391, p=0.000). The study concluded that there was a statistically significant relationship between job sharing, teleworking, and compressed work schedules and employee performance of public universities in the Mount Kenya region. The study recommends that Managers should improve the use of flextime work arrangements because it enhances employee performance, reduces absenteeism, and increases employee satisfaction. Universities should also build flexible arrangements since they help employees in managing their workload and their personal life and help them to assess their responsibilities.s
A Research project submitted in partial fulfillment of the requirements for the conferment of master of Business Administration of Meru University of Science and Technology